Quality of Electronic Student Worksheets on The Concept Ferns (Pteridophyte) to Improve High School Level Critical Thinking Skills - Yunita; Zaini, Muhammad; Kaspul (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2022)
21stcentury learning is an era in which science and technology are developing very rapidly and demand quality human resources and can compete globally. One of the skills that meet the demands of this century is critical thinking skills which are developed through the provision of Student Worksheets. This study aims to describe the validity, practicality, and effectiveness of the e-student worksheet on the concept of Ferns (Pteridophyte) based on Critical Thinking Skills. The subjects of the validity test were three experts, the individual test was three students of class X high school level and the small group test was four students of class X high school level. This type of research is development research to produce valid, practical, and effective products. The results showed that: 1) the validity of the e-student worksheet has a valid category, 2) the practicality of thee-student worksheet has a good category, and 3) the effectiveness of e-student worksheet expectations based on the assessment of students critical thinking skills in doing tasks on thee-student worksheet has a very good category (covering interpretation, analysis, evaluation, inference, and explanation) and good category on self-regulation aspect.